Espaço, tempo e processos de educação informal numa enfermaria - Paula Guimarães (Universidade do Minho, 2002)
When we started the research project Learning in the Workplace, we spent long hours in a hospital ward during the three last months of 1997. This situation led us to experience the space-time duality that influenced professional action in that organisation. In this paper we intend to approach the importance of these two categories in a ward, especially their influence on nurses practices and on informal learning processes.